Wickerhamiella martinezcruziae f. a., sp. nov., a yeast species isolated from tropical habitats. Issue 11 (11th November 2021) - Maciel, Natália O. P.; Santos, Ana R. O.; Felix, Ciro R.; Landell, Melissa F.; Pagani, Danielle M.; Pimenta, Raphael S.; Morais, Paula B.; Angchuan, Jirameth; Wongpanit, Kannika; Srisuk, Nantana; Lachance, Marc-André; Rosa, Carlos A.
Abstract : Four yeast isolates with an affinity to the genus Wickerhamiella were obtained from beach sand, a marine zoanthid and a tree exudate at different localities in Brazil. Two other isolates with almost identical ITS and D1/D2 sequences of the large subunit rRNA gene were isolated from the small intestine of cattle and a grease trap in Thailand. These isolates represent a novel species phylogenetically related to Wickerhamiella verensis, Wickerhamiella osmotolerans, Wickerhamiella tropicalis, Wickerhamiella sorbophila and Wickerhamiella infanticola . The novel species differs by 15–30 nucleotide differences from these species in the D1/D2 sequences. The name Wickerhamiella martinezcruziae f.a., sp. nov. is proposed. The holotype of Wickerhamiella martinezcruziae sp. nov. is CBS 16104 T . The MycoBank number is MB 839328.